Confronting the Bush doctrine : critical views from the Asia-Pacific - Gurtov, Melvin; Van Ness, Peter (Asia's transformations., 2005)
This book focuses on the Bush Doctrine in Asia and examines how the Bush initiatives are received and reacted to in Asia.